2014
DOI: 10.3855/jidc.4696
|View full text |Cite
|
Sign up to set email alerts
|

Low rifampicin concentrations in tuberculosis patients with HIV infection

Abstract: Introduction: The efficacy of tuberculosis (TB) treatment in Human Immunodeficiency Syndrome (HIV) co-infected patients may be compromised by genetic and pharmacokinetic variation in drug disposition. Rifampicin is a critical component of TB treatment. We investigated the influence of drug transporter gene polymorphisms on rifampicin concentrations in TB-HIV co-infected patients in Durban, South Africa. Methodology: Rifampicin concentrations were measured 2.5 hours post-dose (approximated peak, C 2.5hr ) in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 21 publications
4
41
1
Order By: Relevance
“…African populations have shown high levels of host genetic diversity resulting in differences in tuberculosis disease susceptibility . Furthermore, genetic diversity in drug‐metabolizing and drug transport enzymes in the host leads to lower tuberculosis drug concentrations and variation in drug response …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…African populations have shown high levels of host genetic diversity resulting in differences in tuberculosis disease susceptibility . Furthermore, genetic diversity in drug‐metabolizing and drug transport enzymes in the host leads to lower tuberculosis drug concentrations and variation in drug response …”
Section: Resultsmentioning
confidence: 99%
“…79 Furthermore, genetic diversity in drug-metabolizing and drug transport enzymes in the host leads to lower tuberculosis drug concentrations and variation in drug response. [80][81][82] Pharmacogenetics Genetic variation associated with single nucleotide polymorphisms, copy number variants, or insertions or deletions in genes coding for drug-metabolizing and transporter enzymes are increasingly recognized as factors that may affect tuberculosis drug exposure and result in variable pharmacokinetic parameters. 83 Moxifloxacin is metabolized via glucuronide and sulfate conjugation by cytosolic enzymes glucuronosyltransferase and sulfotransferase.…”
Section: Pharmacokinetic Data From Early Phase 1 Studies In Healthy Vmentioning
confidence: 99%
“…Pharmacogenetic polymorphisms are proposed to be an important factor in the high variability in rifampin exposure. More specifically, polymorphisms of the SLCO1B1 gene have been associated with lower rifampin exposure (16,34,42,43). To our knowledge, the potential impact of such polymorphisms in Indonesian TB patients has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple studies have documented the high interindividual variability in C max plasma concentrations of these four agents (condition 4), with levels often (in some studies more than 50 % of the patients) below the normal range for C max values, especially for rifampicin and isoniazid. However, treatment outcome in these studies was in most cases favorable in at least 80 % of the patients [56,61,126,127,[135][136][137]. A systematic review and meta-analysis of 41 studies reporting 2-h post-dose drug concentrations (C 2h ) of the first-line anti-TB drugs showed that in 67, 43, 12, and 27 % of patients, the C 2h levels were below the accepted minimum C max range for rifampicin (<8 μg/ml), isoniazid (<3 μg/ml), pyrazinamide (<35 μg/ml), and ethambutol (<2 μg/ml), respectively [138].…”
Section: Plasma Anti-tb Drug Concentrations and Tdmmentioning
confidence: 99%